Tinjauan Yuridis Tindak Pidana Pendanaan Aktivitas Terorisme Ditinjau dari Undang-Undang Republik Indonesia Nomor 9 Tahun 2013 Tentang Pencegahan dan Pemberantasan Tindak Pidana Pendanaan Terorisme - Agus Aditiya; Muhammad Bangsu (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research is to discuss and analyze the category of criminal acts of terrorist financing in terms of Law of the Republic of Indonesia Number 9 of 2013 concerning Prevention and Eradication of Criminal Acts of Terrorist Financing as well as to discuss and analyze the criminal responsibility of perpetrators of criminal acts of terrorist financing in terms of the Law. -Law of the Republic of Indonesia Number 9 of 2013 concerning Prevention and Eradication of Criminal Acts of Terrorism Funding. This research is included in juridical research. The research results show that an act can be categorized as a criminal act of terrorist financing in terms of Law of the Republic of Indonesia Number 9 of 2013 concerning the Prevention and Eradication of Criminal Acts of Terrorist Financing if it provides, collects, gives or lends funds. The research results also show that the criminal responsibility of perpetrators of terrorist financing crimes is reviewed from the Law of the Republic of Indonesia Number 9 of 2013 concerning the Prevention and Eradication of Terrorism Financing Crimes, namely referring to Article 4, Article 5 and Article 7.